Physiotherapy students' knowledge and attitudes about their role in mental health - Ropafadzo R. Gunduza; Sandy Lord; Monique M. Keller (AOSIS, 2023)
Background: As the prevalence of mental health disorders (MHD) increases, physiotherapy students will be increasingly exposed to patients with MHD in their undergraduate studies. International research has shown that students who have mental health included in their curriculum have more knowledge and positive attitudes towards patients with MHD. In South Africa, little is known about physiotherapy students' attitudes towards and knowledge of mental health. Objectives: To establish the knowledge of and attitudes towards the role of physiotherapy in determining the mental health attitudes. Method: In our cross-sectional, descriptive study, third- and fourth-year physiotherapy students at the University of the Witwatersrand were purposefully sampled. Online questionnaires, based on the Mental Health Knowledge Schedule (MAKS) and Mental Illness Clinicians' Attitudes (MICA) scales were completed. Results: Thirty-four students participated in our study. Overall, all students indicated a moderate level of knowledge and a positive attitude towards mental health with mean MAKS score: 26.94 (standard deviation [s.d.]: 3.57) and MICA-4 score: 39.12 (s.d.: 16.12). Fourth-year students had more knowledge and a better attitude towards mental health when compared to the third-year students. Conclusion: Third- and fourth-year University of the Witwatersrand physiotherapy students have moderate knowledge and a positive attitude towards the role of physiotherapy in mental health. Clinical implications: The inclusion of mental health in the physiotherapy curriculum may improve students' knowledge and attitudes towards mental health and prepare them for managing these complex patients in the future.